PEMBERHENTIAN HAKIM MK ASWANTO, YANG DIDASARKAN PADA DUGAAN KINERJA MENGECEWAKAN DAN KERAP MENGANULIR UNDANG-UNDANG HASIL DPR. - Hartanto, Anton; Indra Jayaprana (Scientium Law Review (SLR), 2025)
The objective of this research is to ascertain the position of the official mechanism for the replacement of Constitutional Court justices according to the Constitutional Court Law, and to understand the constitutional implications of the replacement of Constitutional Court justices by the House of Representatives of the Republic of Indonesia (DPR RI). The research method employed is a normative juridical approach. The findings of this study are as follows: Official Mechanism for the Replacement of Constitutional Court Justices The official mechanism for the replacement of Constitutional Court justices is based on the 1945 Constitution of the Republic of Indonesia and Law No. 24 of 2003 concerning the Constitutional Court. These laws broadly regulate the dismissal of constitutional justices. More specifically, Article 2 of Constitutional Court Regulation (PMK) No. 4/2012 states that constitutional justices can be dismissed under three categories: Honorable discharge, Dishonorable discharge and Temporary suspension. In addition to the aforementioned regulations, the detailed mechanism for the dismissal of constitutional justices is regulated in Constitutional Court Regulation (PMK) No. 4 of 2012 concerning Procedures. Furthermore, Article 23 paragraph (4) of Law No. 7 of 2020 concerning the Third Amendment to Law No. 24 of 2003 concerning the Constitutional Court explains that the dismissal mechanism for constitutional justices is based on a letter submitted by the Chief Justice of the Constitutional Court to the President. The dismissal decree is then issued in the form of a Presidential Decree. This Presidential Decree must be issued within 14 working days from the date the letter from the Chief Justice of the Constitutional Court regarding the dismissal is received. Constitutional Implications of the Replacement of Constitutional Court Justices by the House of Representatives. The constitutional implications of the replacement of Constitutional Court justices by the House of Representatives of the Republic of Indonesia (DPR RI) directly affect the existence of the rule of law and democracy. The research finds that the independence of the judiciary, which is a prerequisite for a state governed by the rule of law and democracy (constitutional democracy), cannot be achieved if the dismissal procedure does not comply with the 1945 Constitution and the Constitutional Court Law. The replacement of constitutional justices that is not carried out through the mechanisms stipulated by the prevailing laws and regulations would undoubtedly be an act of undermining the constitutional mandate. This is because such an action can explicitly disrupt the principle of independence inherent in the Constitutional Court as an institution of judicial power.